Challenges of ISO 19650 Application on Public Health Projects - Chamochumbi Chvedine, Renzo Antonio (2024)
Despite the benefits of Building Information Modeling (BIM), some challenges to implementing it have appeared due to traditional project management, especially in the construction of complex projects. This article presents the challenges to applying ISO 19650:2018 Parts 1 and 2 in public hospital projects in Peru. These challenges were identified through 28 interviews with owners, designers, contractors, suppliers, operators, and final users (doctors and nurses) and complemented by a literature review. The identified challenges were divided into the budget, legal framework, organizational culture, and personnel. The results suggest that the adversities identified in the four groups should be overcome to implement BIM according to the ISO 19650 guidelines. Therefore, recommendations are presented to facilitate the ISO 19650 implementation in public hospital projects.